2015
DOI: 10.1002/jts.22038
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of Dropout From Psychotherapy for Posttraumatic Stress Disorder Among Iraq and Afghanistan Combat Veterans

Abstract: A significant number of veterans of the conflicts in Iraq and Afghanistan have posttraumatic stress disorder (PTSD), yet underutilization of mental health treatment remains a significant problem. The purpose of this review was to summarize rates of dropout from outpatient, psychosocial PTSD interventions provided to U.S. Operation Iraqi Freedom (OIF), Operation Enduring Freedom (OEF), and Operation New Dawn (OND) veterans with combat-related PTSD. There were 788 articles that were identified which yielded 20 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
136
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(157 citation statements)
references
References 44 publications
14
136
7
Order By: Relevance
“…The dropout rate of the control group is consistent with a recent meta-analysis that showed a dropout rate for PTSD psychotherapies of 36% overall (Goetter et al, 2015). Although this study had a small sample size, our results suggest that art therapy may enhance engagement, which would be an important improvement in the treatment of PTSD.…”
Section: Treatment Engagement and Satisfactionsupporting
confidence: 89%
“…The dropout rate of the control group is consistent with a recent meta-analysis that showed a dropout rate for PTSD psychotherapies of 36% overall (Goetter et al, 2015). Although this study had a small sample size, our results suggest that art therapy may enhance engagement, which would be an important improvement in the treatment of PTSD.…”
Section: Treatment Engagement and Satisfactionsupporting
confidence: 89%
“…Previous studies have compared telemedicine to in-person modalities for the treatment of PTSD using cognitive processing therapy with Iraq/Afghanistan veterans (Maieritsch et al, 2015), cognitive processing therapy with female veterans (Morland et al, 2015), and PE among veterans in RCTs (Yuen et al, 2015) and in effectiveness settings (Gross et al, 2011; Tuerk et al, 2010). Further, in relation to attrition, a recent systematic review indicated that drop-out rates did not differ between those who were treated via telemedicine and those treated in-person across samples of veterans who served in Iraq and Afghanistan (Goetter et al, 2015). However, this review did not examine gender differences in attrition or differences based on MST status due to not having an adequate representation of women by which to examine these differences.…”
Section: Methodsmentioning
confidence: 99%
“…129,131-134, 136-138,142,145 Critically, most of these studies reported low dropout rates (0%-29% attrition), 129,[131][132][133][134]137,138,142,[144][145][146] although higher rates were reported by Gallegos and colleagues, 139 (43% dropout) who cited reasons such as difficulty with childcare and transportation among a sample of mostly women of low socioeconomic status. Such low drop-out rates suggest high acceptability of mindfulness-based treatments among individuals with PTSD and are important given that recent studies highlight 35%-40% dropout rates among individuals receiving evidencebased treatments for PTSD (e.g., CPT, PE), [14][15][16] with PE having significantly higher dropout rates. 16 At present, MBSR is the most evidence-supported approach, with 2 RCTs reporting significantly greater improvements in PTSD and related symptomatology with MBSR than with active comparison therapies among veteran populations 137,138 (but see the studies by Kearney and colleagues 133 and Possemato and colleagues 136 ).…”
Section: Mindfulness-based Approaches In the Treatment Of Ptsdmentioning
confidence: 99%
“…13 Moreover, attrition rates for leading treatment interventions were reported to fall between 35% and 40% in recent studies. [14][15][16] In addition, resistance to use interventions incorporating exposure for PTSD has been noted among some clinicians because of, for example, concerns about potential symptom exacerbation. 17 Thus, although traumafocused treatments, including CPT and PE, are considered effective treatments for PTSD, the need for potential adjunctive or alternative treatments is evident.…”
Section: Introductionmentioning
confidence: 99%